Active vibration suppression of payloads with a conical isolator. (May 2014) - Li, H; Hu, SD; Li, HY; Tzou, HS
This article focuses on active vibration isolation of a rigid payload using a conical shell isolator laminated with piezoelectric sensors and actuators. The payload is mounted on the top (minor end) of the conical shell isolator. The piezoelectric sensor is laminated on the inner surface, and the piezoelectric actuator is laminated on the outer surface of the conical shell. The macro-fiber composite piezoelectric material is utilized as the actuator to enhance control performance, and polyvinylidene fluoride actuators are used as a comparison. The mathematical model of the conical isolator and the payload is derived in terms of the sensing signal equation and the actuation equation. Then, the modal equations are transformed into the state-space form with sensing signal as the system output and modal control force as the system input. Linear quadratic controllers are designed for each independent mode. In case studies, axial vibration isolation of the payload is performed to characterize the performance of the conical isolator and the optimal controller.